ORGANIZING EXPERIENTIAL LEARNING ACTIVITIES FOR GLOBAL CITIZENSHIP EDUCATION IN TEACHING CIVIC EDUCATION AT LOWER SECONDARY LEVEL - Thi Thu Ha, Luu (HNUE Journal of Science: Journal of Educational Science, 2026)
This article pursues two main objectives: (1) to analyze the necessity of organizing experiential learning activities for global citizenship education in lower secondary Civic Education; and (2) to propose a set of principles and a procedure for implementing experiential learning aligned with GCE requirements in Civic Education classrooms. For lower secondary Civic Education, experiential learning plays an essential role in connecting knowledge with real-life contexts, enhancing critical thinking, cultivating values and attitudes, and enhancing students’ competency for social engagement. However, the organization of experiential learning activities aligned with GCE remains limited in current practice, particularly due to the lack of well-defined models, implementation procedures, and appropriate assessment tools. The study employs document analysis, synthesis of relevant literature, and secondary data analysis to construct a theoretical foundation and examine the appropriateness of the proposed model. The findings indicate that experiential learning holds significant potential for enhancing GCE outcomes among lower secondary students, and that the proposed principles and procedure can be flexibly applied in the 2018 General Education Curriculum in Vietnam.